Texture analysis of lung nodules in computerized tomography images using functional diversity. (June 2020) - de Oliveira Torres, William; de Carvalho Filho, Antônio Oseas; de Andrade Lira Rabêlo, Ricardo; Veloso e Silva, Romuere Rodrigues
Highlights: An automatic method for reduction of false positives in pulmonary nodule CT images. A new method for characterization of texture. Proposal of a unique texture descriptor based on functional diversity indexes. Tests were applied to a set of 24148 VOIs. Abstract: Although lung cancer is one of the leading causes of cancer deaths worldwide, the chances of survival are higher in the early stages. One of the best tools for diagnosis is computerized tomography. The main problem with this method is that it depends directly on the specialist who is analyzing the image, since the process involved is tiring, and can lead to error. Computer-aided detection systems have emerged as a way to help these specialists. This work presents the use of descriptors based on functional diversity indexes to reduce the number of false positives. Our method can reach an accuracy of 97.73%, a sensitivity of 98.4%, Kappa index of 0.941, and a number of false positives per scan of up to three. Based on the results obtained, the use of a functional diversity index is shown to be a robust method that can be used in a real CAD system.